Comparison of Follicle Isolation Methods for Mouse Ovarian Follicle Culture In Vitro. (August 2018) - Kim, Eun Jung; Lee, Jaewang; Youm, Hye Won; Kim, Seul Ki; Lee, Jung Ryeol; Suh, Chang Suk; Kim, Seok Hyun
Ovarian follicle in vitro culture is a promising fertility preservation option to avoid risk of reintroduction of malignant cells. The objective of this study is to compare 4 different follicle isolation methods from ovarian tissue and evaluate the effect of follicle isolation on further in vitro follicle culture and oocyte competency. Mouse ovaries were dissected and randomly divided into 4 groups according to follicle isolation method: mechanical (MCH) isolation, mincing (MNC) isolation, enzymatically digestion using collagenase (COL), and enzymatically digestion using liberase (LIB). The isolated early secondary follicles were cultured for day 10, and ovulation induction was conducted. Follicular diameter and concentrations of steroid hormone in spent media were measured. Also, follicular survival rate and pseudo-antrum formation rate were examined. After ovulation induction, the cumulus oocyte complexes rate and the number of mature oocyte, normal spindle rate, and mitochondrial activity in ovulated oocyte were counted. After in vitro culture, follicular diameter was significantly greater in MNC and MCH group than other groups. Also, follicle survival rate was significantly higher in MNC and MCH groups than other groups. The MNC group had made a result that significantly improved the mature oocyte rate than other groups. The normal meiotic spindle and chromosome rate is significantly higher in MNC and MCH groups than other groups. The MNC method showed significantly improved rate of follicle diameter, survival, pseudo-antrum formation, a mature oocyte, and normal spindle in ovulated oocyte after in vitro culture. Based on the results, MNC method can be an alternative for MCH method that is laborious and time-consuming.